If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3 + -1y) = -3x + 4 (3 * 7 + -1y * 7) = -3x + 4 (21 + -7y) = -3x + 4 Reorder the terms: 21 + -7y = 4 + -3x Solving 21 + -7y = 4 + -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -7y = 4 + -21 + -3x Combine like terms: 21 + -21 = 0 0 + -7y = 4 + -21 + -3x -7y = 4 + -21 + -3x Combine like terms: 4 + -21 = -17 -7y = -17 + -3x Divide each side by '-7'. y = 2.428571429 + 0.4285714286x Simplifying y = 2.428571429 + 0.4285714286x
| 21x+6=17x-16 | | -d^2+18d-81=0 | | -13X+20=-11 | | (5x-20)=3x | | 7h-3h-6=6 | | 5(x-1)(x+4)(2x-3)=0 | | -2=-1.75k | | 25=5(9x-4) | | 2x-9=6x-13 | | -2(3)+5+5(3)= | | 6x-2=12x+1 | | 2x^3-3x-20=0 | | y-(-16)=-12 | | -18+30=-4(x+5) | | x+(-24)=-38 | | -4(x+3)=4 | | 1x/19=20 | | .42*n=.6 | | 8-5x-6-9x=4 | | x(2x+5)=0 | | 6x+3=6x+2x-21 | | -14=-3x-65 | | -9(x+3)-(1+4x)=-14x | | f(-2)=1+5(-2) | | 198=(x+11)(x) | | x+2=3(2x-6) | | 6k-24=7-2k | | 3t=3t-21 | | 2(2x-5)=3(x+2) | | -7+n=8 | | 6r-4-2r=8r-4 | | 1-5x=-39 |